Serum Interleukins as Potential Prognostic Biomarkers in HBV-Related Acute-on-Chronic Liver Failure - Lili Zhang; Jianhua Hu; Chunyan Gou; Hua Jin; Chun Zhang; Yang Liu; Yitong Wang; Xiaojun Wang (Mediators of Inflammation)
Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is relatively common in China and has complex pathogenesis, difficult clinical treatment, and poor prognosis. Immune status is an important factor affecting ACLF prognosis. Interleukins are a family of secreted lymphocyte factors that interact with a host of cell types including immune cells. These signaling molecules play important roles in transmitting information; regulating immune cells; mediating the activation, proliferation, and differentiation of T and B cells; and modulating inflammatory responses. Many studies have investigated the correlation between interleukin expression and the prognosis of HBV-ACLF. This review focuses on the potential use of interleukins as prognostic biomarkers in HBV-ACLF. References were mainly identified through PubMed and CNKI search, including relevant studies published until December 2021. We have summarized reports of several promising diagnostic interleukin biomarkers that predict susceptibility to HBV-ACLF. The use of biomarkers to understand early prognosis can help devise different therapeutic measures and improve patient survival. Ongoing research on prognostic biomarkers of HBV-ACLF is promising, and future preclinical and clinical studies are warranted.